Gamification of Al-Khawarizmi Number Basis Module for Gifted and Talented Muslim Students - Norazlina Subani; Hadif Syahuputra Syahizam; Akif Zafran Normanhisham; Farith Akhtar Rahmat; Akil Naeem Muslim; Muhammad Adam Irfan Sharizan (Universiti Sains Islam Malaysia, 2024)
Malaysian Journal of Science Health & Technology, Volume 10 Issue 2 Page (117–124)